Effects of pore water chemistry on hydraulic conductivity of saturated loess - F.Y. Zhang; J.X. Zhang (International Association of Lowland Technology, 2018)
The effects of pore water chemistry on hydraulic conductivity of saturated loess are investigated. A series of laboratory tests were conducted to investigate these effects with different salt concentrations, cations, and anions. The results showed that with increased NaCl concentration, the hydraulic conductivity of the loess samples decreased below 14%, but an increase occurred at 16%. The hydraulic conductivity of loess samples with different cations in the permeant decreased in the following order: Ca2+ > K+ > Na+, which was mainly affected by the different valence and hydrated ion radius thereof. The effects of different anions on loess permeability were influenced by their ability to influence the activity of cations, and the hydraulic conductivities were in order: Cl- > SO4 2- > HCO3 - . To investigate the major mechanisms involved in variations in hydraulic conductivity, the trends in sample hydraulic conductivity and intrinsic permeability to different salt solutions were compared. The similar plots revealed that the changes in hydraulic conductivity were attributed to changes in soil fabric, which was due to the change of electric double layer thickness and charge characteristics of certain soil mineral surfaces and edges, rather than the density and viscosity of those permeating fluids. In addition, the implications for water-induced hazards were also discussed.